Design and Analysis of a Low Power Tri-Gate Trapezoidal Finfet - Musalgaonkar, Gaurav (My University, 2015)
In the recent years non-planer tri-gate (TG) field-effect transistors (FETs) such as FinFETs has been considered as the best option for the sub-50 nm regime of MOSFETs due to their better gate control, reduced short channel effects (SCEs), better scalability and improved performance over bulk planar MOSFETs. This dissertation work presents the design and comparison of a Trapezoidal FinFET (Tz-TGFinFETs) and Rectangular FinFET (ReTGFinFET’s) using COGENDA GENIUS VISUAL TCAD tool. Firstly, a ReTGFinFET structure has been studied for different substrate doping concentration. Next, by varying the ReTGFinFET’s sidewall inclination angle a trapezoidal FinFET has been obtained. This structure has been studied taking different inclination angles. Various parameters such as threshold voltage, transconductance, drain current, has been calculated and compared with those of rectangular FinFET. It is observed that the trapezoidal FinFET gives better performance and reduced corner effect for an optimum doping concentration as compared to the rectangular FinFET. Further in multifin FinFET, to show the effect of doping concentration over threshold voltage an analytic expression have been obtained and validated by numerical simulations.
ME, ECED
Keywords: Rectangular FINFET; Trapezoidal FINFET; Corner Effects; MOSFET; Low Power; TCAD